If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/3)*(x-2) = 2*x-(13/3) // - 2*x-(13/3)
(1/3)*(x-2)-(2*x)+13/3 = 0
(1/3)*(x-2)-2*x+13/3 = 0
1/3*(x-2)-2*x+13/3 = 0
(1/3*3*(x-2))/3+(-2*3*x)/3+13/3 = 0
1/3*3*(x-2)-2*3*x+13 = 0
13-5*x-2 = 0
11-5*x = 0
(11-5*x)/3 = 0
(11-5*x)/3 = 0 // * 3
11-5*x = 0
11-5*x = 0 // - 11
-5*x = -11 // : -5
x = -11/(-5)
x = 11/5
x = 11/5
| 4u-12=-6(u+7) | | -8/9y=7 | | 5(x+15)=5x+75 | | 4R-4y-8= | | n-17.2=-2.3 | | 4x^2+9+12x=18 | | 12st/4t | | 9x-6y=12 | | -103=2x+6x-7 | | 2(x+5)=2(x+15) | | m-22/6-7m-21/7=1 | | 10y+2y-12=3(4-6y) | | A-4/512 | | 2x-5=10x-5 | | n/3=4n= | | 2(14+8a)=9a | | 25x-10x-6=0 | | 3(x+1)=6y+11 | | 3(3b-5)= | | .75x-2.75=.3x+.83 | | [4x-4]=12 | | 10-66p=52 | | 2(u+3v)=w-50 | | 2+5-6+x=10 | | (a/3)=((a-3)/2) | | 9x==2/3 | | 2x+4y-4z=-12 | | (a/3)/((a-3)/2) | | 20=a(a-8) | | 2x+6=8+5x | | 450/0.09 | | [7x-7]=21 |